Diagnosis and management of allergy and respiratory disorders in sport: An EAACI task force position paper. Issue 10 (23rd July 2022) - Price, Oliver J.; Walsted, Emil S.; Bonini, Matteo; Brannan, John D.; Bougault, Valérie; Carlsen, Kai‐Håkon; Couto, Mariana; Kippelen, Pascale; Moreira, André; Pite, Helena; Rukhadze, Maia; Hull, James H.
Abstract: Allergy and respiratory disorders are common in young athletic individuals. In the context of elite sport, it is essential to secure an accurate diagnosis in order to optimize health and performance. It is also important, however, to consider the potential impact or consequences of these disorders, in recreationally active individuals engaging in structured exercise and/or physical activity to maintain health and well‐being across the lifespan. This EAACI Task Force was therefore established, to develop an up‐to‐date, research‐informed position paper, detailing the optimal approach to the diagnosis and management of common exercise‐related allergic and respiratory conditions. The recommendations are informed by a multidisciplinary panel of experts including allergists, pulmonologists, physiologists and sports physicians. The report is structured as a concise, practically focussed document, incorporating diagnostic and treatment algorithms, to provide a source of reference to aid clinical decision‐making. Throughout, we signpost relevant learning resources to consolidate knowledge and understanding and conclude by highlighting future research priorities and unmet needs. Abstract :